Spontaneous Bacterial Peritonitis - Abimanyu Abimanyu (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2003)
Infected ascites is one of the complication happened in liver cirrhotic patient in ascites. There are 5 infected ascites classifications i.e. Spontaneous Ascites Infection Consist of Spontaneous Bacterial Peritonitis, Monomicrobial Non Neurocytic Bacteriascites, Culture Negative Neurocytic Ascites, Secondary Bacterial Peritonitis and Iantrogenic Polimicrobial Bacterascites. Spontaneous Bacterial Peritonitis (SBP) is the infection in ascites without unrecognized intra abdominal infection source.The normal floras in the gastrointestinal, respiratory or urinal tract are the important infection source in SBP. As we know that normal ascites has ability to kill micro organism through phagocitosis function, opsonization, but when infected occurs ; phagocitosis function, opsonization, and MPS could be worst so that the possibility of being SBP increased. The common frequently sign and symptom of SBP are fever, abdominal pain, consciousness assault, tenderness, diarrhea, paralytic ileus, hypotension and hypothermia. Some of the invasive actions like endoscopy, variceal sclerotherapy and ligation may cause intestine flora translocation to mesenteric gland, bacterimia and infected ascites also made transmural passage intestine micro organism to ascites may cause infected ascites. Cefotaxime is the antibiotic that more frequently studied to SBP patient. The dose of cefotaxime to SBP patient show that 2 gram/6 hours and 2 gram/12 hours injected produce SBP resolution and the same survival, besides that 2 gram/8 hours injected for 5 and 10 days also show the same effectively. The antibiotic prophylaxis such as quinolon group show the effective result in liver cirrhotic with the gastroentestinal tract bleeding and low total protein (1 gram/dl ) or has the SBP experience patients.